Historical occurrence of Antarctic icebergs within mercantile shipping routes and the exceptional events of the 1890s - Headland, Robert Keith; Hughes, Nicholas Edward; Wilkinson, Jeremy Paul (Journal of Glaciology, 2023)
A major consideration for maritime activity in the Southern Hemisphere is the northern limit of icebergs, or the Southern Ocean Limit Of Known Ice (SOLOKI). This analysis of historical reports of icebergs during Southern Hemisphere voyages from 1687 to 1933 provides a basis for examination of their geographical and chronological occurrence during ~250 years. The analyses use tabulated data from 742 voyages and other reports from many sources, some including first-person descriptions. While these data are dependent on icebergs being reported by mariners, as well as the variable frequency of voyages, they demonstrate distinct periods of exceptional frequency of icebergs occurring in certain localities, particularly the far South Atlantic. Based upon historical records the evidence suggests unprecedented numbers of icebergs were present in southern shipping channels in the 1890s. When these historical observations are combined with modern iceberg drift trajectories, their possible origin can be elucidated. Owing to the numbers of icebergs seen and their geographical spread, our results suggest that this was possibly the largest near-synchronous calvings in the last 300 years, and the northernmost extent of the SOLOKI.
Keywords: Sørishavet; glasiologi; isfjell

Three-decade spatial patterns in surface mass balance of the Nivlisen Ice Shelf, central Dronning Maud Land, East Antarctica - Pratap, Bhanu; Dey, Rahul; Matsuoka, Kenichi; Moholdt, Geir; Lindbäck, Katrin; Goel, Vikram; Laluraj, C M; Thamban, Meloth (Journal of Glaciology, 2022)
The coastal Droning Maud Land in East Antarctica is characterized by small ice shelves with numbers of promontories and locally grounded isles, both called ice rises. These ice rises are typically dome-shaped and surface elevations are hundreds of meters above the surrounding ice shelves, which cause strong orographic effects on surface mass balance (SMB). We conducted shallow ice-penetrating radar sounding to visualize firn stratigraphy in the top 35 m over ~400 km of profiles across the Nivlisen Ice Shelf, and in a grid pattern over two adjacent ice rises (Djupranen and Leningradkollen). We tracked six reflectors (isochrones) and dated them using two ice cores taken at the ice rise summits, from which SMB over six periods in the past three decades was retrieved. The overall SMB pattern across the ice shelf remained similar for all periods; however, the eastwest contrast in SMB varies by a factor of 1.5–2 between the Leningradkollen and Djupranen grounding lines. The SMB patterns over the ice rises are more varied owing to complex interactions between topography, snowfall and wind. We use our results to evaluate the regional climate model RACMO2.3p2 in terms of the spatial SMB distribution and temporal changes over the ice shelf and ice rises at regional scale.
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; glasiologi; isshelf; stratigrafi

Characteristics of ice rises and ice rumples in Dronning Maud Land and Enderby Land, Antarctica - Goel, Vikram; Matsuoka, Kenichi; Berger, Cesar Deschamps; Lee, Ian; Dall, Jørgen; Forsberg, René (Journal of Glaciology, 2020)
Ice rises and rumples, locally grounded features adjacent to ice shelves, are relatively small yet play significant roles in Antarctic ice dynamics. Their roles generally depend upon their location within the ice shelf and the stage of the ice-sheet retreat or advance. Large, long-stable ice rises can be excellent sites for deep ice coring and paleoclimate study of the Antarctic coast and the Southern Ocean, while small ice rises tend to respond more promptly and can be used to reveal recent changes in regional mass balance. The coasts of Dronning Maud Land (DML) and Enderby Land in East Antarctica are abundant with these features. Here we review existing knowledge, presenting an up-to-date status of research in these regions with focus on ice rises and rumples. We use regional datasets (satellite imagery, surface mass balance and ice thickness) to analyze the extent and surface morphology of ice shelves and characteristic timescales of ice rises. We find that large parts of DML have been changing over the past several millennia. Based on our findings, we highlight ice rises suitable for drilling ice cores for paleoclimate studies as well as ice rises suitable for deciphering ice dynamics and evolution in the region.
Keywords: Antarktis; Dronning Maud Land; Sørishavet; glasiologi; isshelf

High-resolution distributed vertical strain and velocity from repeat borehole logging by optical televiewer: Derwael Ice Rise, Antarctica - Hubbard, Bryn; Philippe, Morgane; Pattyn, Frank; Drews, Reinhard; Young, Tun Jan; Bruyninx, Carine; Bergeot, Nicolas; Fjøsne, Karen; Tison, Jean-Louis (Journal of Glaciology, 2020)
Direct measurements of spatially distributed vertical strain within ice masses are scientifically valuable but challenging to acquire. We use manual marker tracking and automatic cross correlation between two repeat optical televiewer (OPTV) images of an ~100 m-long borehole at Derwael Ice Rise (DIR), Antarctica, to reconstruct discretised, vertical strain rate and velocity at millimetre resolution. The resulting profiles decay with depth, from −0.07 a−1 at the surface to ~−0.002 a−1 towards the base in strain and from −1.3 m a−1 at the surface to ~−0.5 m a−1 towards the base in velocity. Both profiles also show substantial local variability. Three coffee-can markers installed at different depths into adjacent boreholes record consistent strain rates and velocities, although averaged over longer depth ranges and subject to greater uncertainty. Measured strain-rate profiles generally compare closely with output from a 2-D ice-flow model, while the former additionally reveal substantial high-resolution variability. We conclude that repeat OPTV borehole logging represents an effective means of measuring distributed vertical strain at millimetre scale, revealing high-resolution variability along the uppermost ~100 m of DIR, Antarctica.
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf

Formation and evolution of an extensive blue ice moraine in central Transantarctic Mountains, Antarctica - Kassab, Christine M; Licht, Kathy J; Petersson, Rickard; Lindbäck, Katrin; Graly, Joseph A; R, Kaplan. Michael (Journal of Glaciology, 2020)
Mount Achernar moraine is a terrestrial sediment archive that preserves a record of ice-sheet dynamics and climate over multiple glacial cycles. Similar records exist in other blue ice moraines elsewhere on the continent, but an understanding of how these moraines form is limited. We propose a model to explain the formation of extensive, coherent blue ice moraine sequences based on the integration of ground-penetrating radar (GPR) data with ice velocity and surface exposure ages. GPR transects (100 and 25 MHz) both perpendicular and parallel to moraine ridges at Mount Achernar reveal an internal structure defined by alternating relatively clean ice and steeply dipping debris bands extending to depth, and where visible, to the underlying bedrock surface. Sediment is carried to the surface from depth along these debris bands, and sublimates out of the ice, accumulating over time (>300 ka). The internal pattern of dipping reflectors, combined with increasing surface exposure ages, suggest sequential exposure of the sediment where ice and debris accretes laterally to form the moraine. Subsurface structure varies across the moraine and can be linked to changes in basal entrainment conditions. We speculate that higher concentrations of debris may have been entrained in the ice during colder glacial periods or entrained more proximal to the moraine sequence.
Keywords: Antarktis; glasiologi; radar observasjoner

Life of the Antarctic ice : from deep inland to the coast - Matsuoka, Kenichi (ed.) (Norwegian Polar Institute, 2020)
Keywords: Antarktis; Dronning Maud Land; glasiologi; innlandsis; isbreer; klimaendringer; polarforskning; snø

A Mobile, Multichannel, UWB Radar for Potential Ice Core Drill Site Identification in East Antarctica: Development and First Results - Rodriguez-Morales, Fernando; Braaten, David; Trong Mai, Hoang; Paden, John; Gogineni, Prasad; Yan, Jie-Bang; Abe-Ouchi, Ayako; Fujita, Shuji; Kawamura, Kenji; Tsutaki, Shun; Liefferinge, Brice Van; Matsuoka, Kenichi; et al. (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2020)
We developed a high-performance, multichannel, ultra-wideband radar system for measurements of the base and interior of the East Antarctic Ice Sheet. We designed the radar to be of high power (4000-W peak) yet portable and to be able to operate with 60-MHz bandwidth at a center frequency of 200 MHz, providing high sensitivity and fine vertical resolution relative to current technology. We used the radar to perform extensive measurements as a part of a multinational collaboration. We collected data onboard a tracked vehicle outfitted with an array of high-gain antennas. We sounded 2- to 3-km thick ice near Dome Fuji. Preliminary ice thickness data match those obtained via semicoincident measurements performed with a different surface-based pulse modulated radar system operated during the same field campaign, as well as previous airborne measurements. In addition, we mapped internal reflection horizons with fine vertical resolution from 300 m below the ice surface to ∼100 m above the bed. In this article, we provide a detailed overview of the radar instrument design, implementation, and field measurement setup. We present sample data to illustrate its capabilities and discuss how the data collected with it will be valuable for the assessment of promising drilling sites to recover ice cores that are 0.9–1.5 million years old.
Keywords: Antarktis; glasiologi; innlandsis; iskjerner